The Effect of Game Strategi and Storytelling Strategi on Listening Skills for Grade VI Students - Siti Hajar; Rahmad Husein; Juhana Juhana (Mahesa Research Center, 2021)
This study aims to determine the effect of game strategies and storytelling strategies on Indonesian Language lessons on listening skills of Grade VI students of State Elementary School No.118315, Negerilama Plantation. This type of research is a semi-experimental study with a sample of 2 experimental classes, namely 20 students of class VI A and 22 students of class VI B. Class VI A was treated with Game Strategy and Class VI B was treated with Storytelling Strategy. The research instrument used a test consisting of 5 questions in the form of an essay test that has been tested for validity and reliability. After being given treatment to the two experimental classes, the results are (1) There were differences in students' listening skills before and after being given the game strategy treatment in class VI, namely 75.5 and 83.5. (2) There are differences in students' listening skills before and after being given storytelling strategy treatment in class VI, namely 67.8 and 76.6. (3) Listening skills of grade VI students were better at using game strategies than storytelling strategies. This was indicated by the average listening skill of students using game strategy was 83.5 while storytelling strategy were 76.6.